Relevance of the Employee's Experience in the Achievement of Organizational Goals - Cueva Talledo, Joyce Marivi (2023)
The aim of this article is to examine six models of employee experience as proposed by various authors and members of world-renowned consulting agencies, to specify the dimensions and practices related to each model as part of human resource management, and to find their relevance for the achievement of organizational objectives. The results of the literature review, carried out by searching for scientific papers on Scopus, revealed which models are most commonly referenced by other researchers, and made it possible to study the schemes proposed in more detail, as well as finding out the relevance of employee experience in the improvement of key indicators such as commitment, innovation, and performance. The study concluded that organizations need to create a more empathic and significant connection with their employees, in such a way that the effort and investment made is not only focused on their clients' desires, expectations and needs, but also on the employees', to design an organization based on experience and generate strong employee involvement in the achievement of organizational objectives.